Isolation and molecular characterization of vancomycinresistant Enterococcus faecium in Malaysia - Son, Radu; Nimita, F.; Rusul, G.; Nasreldin, E.; Samuel, Lihan; Nishibuchi, M. (The Society for Applied Microbiology, 1999)
Nineteen strains of vancomycin-resistant Enterococcus faecium isolated from 10 of 75 (13·3%) tenderloin beef samples were examined for resistance to selected antibiotics, presence of plasmids, and genetic diversity by random amplification of polymorphic DNA analysis. All strains showed multiple resistant to the antibiotics tested. Multiple antibiotic indexing of the vancomycin-resistant E. faecium strains showed that all (100%) originated from high risk contamination environments where antibiotics were often used. Plasmids ranging in size from 1·5 to 36 megadalton were detected in 15 of 19 (79%) strains. Thus, three plasmid profiles and eight antibiotypes were observed among the E. faecium strains. A high degree of polymorphism was obtained by combining the results of the two primers used; with the 19 E. faecium strains being differentiated into 19 RAPD-types. These preliminary results suggest that RAPD-PCR has application for epidemiologic studies and that resistance patterns and plasmid profiling could be used as an adjunct to RAPD for the typing of E. faecium in the study area.